GmDAD1, a Conserved Defender Against Cell Death 1 (DAD1) From Soybean, Positively Regulates Plant Resistance Against Phytophthora Pathogens - Yan, Qiang; Si, Jierui; Cui, Xiaoxia; Peng, Hao; Jing, Maofeng; Chen, Xin; Xing, Han; Dou, Daolong (Frontiers in Plant Science, 2019)
Initially identified as a mammalian apoptosis suppressor, defender against apoptotic death 1 (DAD1) protein has conserved plant orthologs acting as negative regulators of cell death. The potential roles and action mechanisms of plant DADs in resistance against Phytophthora pathogens are still unknown. Here, we cloned GmDAD1 from soybean and performed functional dissection. GmDAD1 expression can be induced by Phytophthora sojae infection in both compatible and incompatible soybean varieties. By manipulating GmDAD1 expression in soybean hairy roots, we showed that GmDAD1 transcript accumulations are positively correlated with plant resistance levels against P. sojae. Heterologous expression of GmDAD1 in Nicotiana benthamiana enhanced its resistance to Phytophthora parasitica. NbDAD1 from N. benthamiana was shown to have similar role in conferring Phytophthora resistance. As an endoplasmic reticulum (ER)-localized protein, GmDAD1 was demonstrated to be involved in ER stress signaling and to affect the expression of multiple defense-related genes. Taken together, our findings reveal that GmDAD1 plays a critical role in defense against Phytophthora pathogens and might participate in the ER stress signaling pathway. The defense-associated characteristic of GmDAD1 makes it a valuable working target for breeding Phytophthora resistant soybean varieties.